Dinamika Struktur Modal dalam Perusahaan Sektor Tambang: Pengaruh Struktur Aset, Kepemilikan Institusional, Risiko Bisnis dan Growth Opportunity - Dewi, Tri Marliana; Waskito, Jaka; Amin, M. Arridho Nur (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
This study aims to analyze the impact of asset structure, institutional ownership, business risk, and growth opportunity on the capital structure of mining companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024. The research approach employed is a quantitative method utilizing secondary data from financial statements obtained through the official portal of the Indonesia Stock Exchange. The population consists of 63 mining companies, with a sample of 17 companies selected through purposive sampling. The data analysis technique used is multiple linear regression analysis using SPSS 25. Several previous studies have shown inconsistent findings regarding the effects of asset structure, institutional ownership, business risk, and growth opportunity on capital structure, particularly among mining sector companies listed on the IDX during the 2020 to 2024 period, a time marked by post-pandemic recovery and fluctuations in global commodity prices. The novelty of this study lies in the simultaneous testing of these four independent variables within a single model in the context of the mining industry, an area that has not been extensively explored in previous research. The findings reveal that asset structure, institutional ownership, and business risk have a significant negative effect on capital structure, while growth opportunity has no significant effect on capital structure. Collectively, the four independent variables have a simultan effects on capital structure.